The Application of Moderate Politeness into School Practices of An Urban Muhammadiyah Primary Students in The Era of Global Communication - Riyanto, Sugeng; Prayitno, Harun Joko; Fauzan, Fauzan; Huda, Miftachul; Yuniawan, Tommi (International Journal of Language Education, 2023)
Language politeness is considered one of the defining characteristics of Indonesian society. In the age of global communication and computing, moderate politeness, centered on politeness of opinion, politeness in deliberation, and politeness in respecting the opinions of others, is an important factor. However, progressive politeness in Urban Muhammadiyah Primary School is becoming a growing concern that requires special attention. The purpose of this study was to examine this violation in the interactions between learners, teachers, and principals in Yogyakarta, Indonesia. This study adopts a qualitative approach with a case study design. The data were collected from interviews, observations, and documentation. Interviews were conducted with classroom teachers, principals, and learners, while observations were recorded through field notes and reflections. Moreover, audio-visual documentation in the form of photographs, videos, and recordings during the learning processes and interactions between learners or teachers were utilized. Data collection was based on four strategies: observation, interview, documents, and audio-visual, as outlined in Creswell's theory. Validity was examined using data triangulation, member checking, prolonged duration of data collection, repeated observations in the study location, and peer examination. The findings of the study include a) There was a violation of the politeness through bullying, body shaming, and verbal abuse, which violated the principles of appreciation and sympathy. b) Urban Muhammadiyah Primary School helped promote language politeness through several methods, including performing Duha prayers, morning recitation with assistance from the teacher and principal, and teacher role modelling by arriving at school at 06.15 and reciting Asmaul Husna together. Importantly, these efforts positively affected the politeness of the learners. This study provides an update on the assistance given to learners to address impoliteness, including Duha prayers, morning recitation, and memorization of Al-Qur'an and Asmaul Husna assisted by teachers. Moreover, the school has a well-equipped School Health Unit (SHU) to promote a healthy, clean, disciplined, and polite lifestyle. Appeals are made through persuasive and affectionate books and direct assistance from teachers as role models. The study of the Quran and Asmaul Husna demonstrates children's moderate politeness in expressing their opinions. The agreement to develop a joint discipline demonstrates the children's moderate politeness in deliberation.